2016
DOI: 10.1128/aem.00337-16
|View full text |Cite
|
Sign up to set email alerts
|

Use of Colistin and Other Critical Antimicrobials on Pig and Chicken Farms in Southern Vietnam and Its Association with Resistance in Commensal Escherichia coli Bacteria

Abstract: Antimicrobial resistance (AMR) is a global health problem, and emerging semi-intensive farming systems in Southeast Asia are major contributors to the AMR burden. We accessed 12 pig and chicken farms at key stages of production in Tien Giang Province, Vietnam, to measure antimicrobial usage and to investigate the prevalence of AMR to five critical antimicrobials (β-lactams, third-generation cephalosporins, quinolones, aminoglycosides, and polymyxins) and their corresponding molecular mechanisms among 180 Esche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
145
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(178 citation statements)
references
References 26 publications
17
145
4
1
Order By: Relevance
“…Six publications [15,16,17,18,19,20] reported AMU in terrestrial animal production (pigs and chickens), and two in aquaculture production [21,22]. Except for one publication that investigated antimicrobial use to raise chickens in integrated fish–chicken farms [21] in Thailand, and another one that investigated fish and shrimp farms in both Thailand and Vietnam [22], the remaining publications investigated AMU exclusively in Vietnamese farms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six publications [15,16,17,18,19,20] reported AMU in terrestrial animal production (pigs and chickens), and two in aquaculture production [21,22]. Except for one publication that investigated antimicrobial use to raise chickens in integrated fish–chicken farms [21] in Thailand, and another one that investigated fish and shrimp farms in both Thailand and Vietnam [22], the remaining publications investigated AMU exclusively in Vietnamese farms.…”
Section: Resultsmentioning
confidence: 99%
“…All studies report types and classes of antimicrobials used on farms over a specified period of time. In three publications (two of which relate to the same study farms), quantitative data are also presented [16,18,23]. In two of these studies [16,18] consumption is presented in terms of grams of antimicrobial compound to produce one kilogram of chicken or pig produced, whereas in the other [23], consumption for chickens was expressed as “treatment incidence” [24].…”
Section: Resultsmentioning
confidence: 99%
“…The gene is also present in Enterobacteriaceae from food animals in Vietnam (155,156), with up to 22% of E. coli isolates from 6 each of pig and chicken farms testing positive in a study conducted between 2013 and 2014 (155). Other countries of Southeast Asia.…”
Section: Vietnam There Is No National or Regional Antimicrobial Resimentioning
confidence: 99%
“…In pigs, the mcr-1 gene was isolated mainly from colistin resistant E. coli strains with variable prevalence between countries; China (20.6%), Vietnam (22%), Belgium (13.2%), Brazil (2%), Spain (0.68%), Germany (0.51%), and France (0.50%) (Falgenhauer et al, 2016; Fernandes et al, 2016; Liu et al, 2016; Malhotra-Kumar et al, 2016a; Nguyen et al, 2016; Perrin-Guyomard et al, 2016; Quesada et al, 2016). Most recently, in the USA pig production, the mcr-1 gene was identified for the first time in a colistin resistant E. coli strain isolated from a pig from South Carolina (Meinersmann et al, 2016).…”
Section: Mechanisms Of Enterobacteriaceae Resistance To Colistinmentioning
confidence: 99%
“…Almost all studies conducted on pigs worldwide to screen mcr-1 gene presence in enterobacterial species reported that colistin resistant strains harboring this gene also showed resistance to one or several classes of antibiotics conventionally used in swine such as: Aminoglycoside, Sulfonamide, Trimethoprim, Tetracycline, Quinolone, Lincosamide, β-lactam, and third generation cephalosporin (Anjum et al, 2016; Falgenhauer et al, 2016; Malhotra-Kumar et al, 2016b; Nguyen et al, 2016). This multi-resistance of mcr-1 positive E. coli strains in pigs was associated with the presence of a sul3 -containing class 1 integron, In 640 , in the plasmid’s mediated mcr-1 gene.…”
Section: Mechanisms Of Enterobacteriaceae Resistance To Colistinmentioning
confidence: 99%